The Impact Of Nutmeg Company Closure On Workers Social, Economic And Environmental Changes (Case Study Of PT.Ollop, Hila Village, Leihitu Sub-District, Central Maluku District) - ali abdila Tatisina; Jeter Donald Siwalette; Noviar F. Wenno (Cita konsultindo, 2024)
The closure of a nutmeg company that has been established for 10 years can have an impact on social, economic and environmental life, especially workers who have been dependent on the company to be able to fulfill aspects of their lives. This study aims to determine the social, economic and environmental impacts of PT Ollop workers in Hila Village due to the closure of PT Ollop. And whether there are changes for PT. Ollop workers in Hila Village related to the presence of the company until the company stopped operating in 2016. This research was conducted for two months, namely in August-September 2023. this research uses a qualitative approach with a case study strategy. In determining informants in this study, purposive sampling with snowball technique was determined. The data analysis method used is qualitative descriptive analysis. The impact of PT Ollop's cessation of operations can be seen from changes in interactions between communities, family values, increased knowledge and access to education, health, changes in livelihoods, income, expenses, work environment and living environment.